2013
DOI: 10.3892/mmr.2013.1834
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid inhibits tumor angiogenesis in mice transplanted with Kasumi-1 leukemia cells

Abstract: Histone deacetylase (HDAC) inhibitors have been reported to inhibit tumor angiogenesis via the downregulation of angiogenic factors. Our previous in vitro studies demonstrated that valproic acid (VPA) exerted antitumor effects on Kasumi-1 cells, which are human acute myeloid leukemia cells with an 8;21 chromosome translocation. In the present study, the effects of VPA on tumor angiogenesis were investigated in mice transplanted with Kasumi-1 cells. Semi-quantitative reverse transcription-polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Ginsenoside Rg3 has been not only used in antiangiogenic therapy of solid tumors, but also exhibits an anti-leukemia effect in part due to its anti-angiogenic activity via inhibiting PI3K/Akt and ERK1/2 pathways, which act to regulate expression of HIF-1α and VEGF (30). Histone deacetylase (HDAC) inhibitors have been reported to inhibit tumor angiogenesis via downregulation of angiogenic factors (31). The mechanism underlying VPA induced antiangiogenesis is associated with suppression of VEGF and its receptors (31).…”
Section: C-myc As An Important Tumor Angiogenesis Factor In Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside Rg3 has been not only used in antiangiogenic therapy of solid tumors, but also exhibits an anti-leukemia effect in part due to its anti-angiogenic activity via inhibiting PI3K/Akt and ERK1/2 pathways, which act to regulate expression of HIF-1α and VEGF (30). Histone deacetylase (HDAC) inhibitors have been reported to inhibit tumor angiogenesis via downregulation of angiogenic factors (31). The mechanism underlying VPA induced antiangiogenesis is associated with suppression of VEGF and its receptors (31).…”
Section: C-myc As An Important Tumor Angiogenesis Factor In Leukemiamentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors have been reported to inhibit tumor angiogenesis via downregulation of angiogenic factors (31). The mechanism underlying VPA induced antiangiogenesis is associated with suppression of VEGF and its receptors (31). Furthermore, the combined use of histone deacetylase inhibitor VPA, all-trans retinoic acid (ATRA), and deoxyribonucleic acid polymerase-α inhibitor cytarabine (Ara-C) is now considered for disease-stabilizing treatment of AML, which was related to antiproliferative effects, and modulation of release of angiogenic mediator of endothelial helix-loop-helix leucine zipper transcription factor can be attributed to c-myc (41).…”
Section: C-myc As An Important Tumor Angiogenesis Factor In Leukemiamentioning
confidence: 99%
“…One of the HDAC inhibitors is valproic acid (VPA), which has been widely used for the treatment of epilepsy [ 25 ]. Several studies have shown that VPA also inhibits tumor angiogenesis through suppression of angiogenic factors such as VEGF [ 26 27 ]. While HDACIs have been widely used in cancer treatment, these agents have yet to be applied to the treatment of ophthalmic disease [ 28 29 30 ].…”
mentioning
confidence: 99%
“…The inhibitors of HDACs render cancer cells more sensitive to immunotherapy, increasing the expression of antigens present in the tumor and thus acting as immunomodulators [ 192 ]. The anticancer activity of HDACis comprises different molecular and physiological events such as the inhibition of the vascular endothelial growth factor (VEGF), endothelial nitric oxide synthase (eNOS) and TGFβ1 [ 193 , 194 , 195 ]. The apoptosis of tumor cells induced by HDACis is associated with their ability to selectively regulate proapoptotic pathways [ 196 ], which does not occur in normal cells [ 197 ].…”
Section: Inhibitors Of Hdacsmentioning
confidence: 99%